Incidence and Etiology of Drug-Induced Liver Injury in Mainland China - Shen, Tao; Liu, Yingxia; Shang, Jia; Xie, Qing; Li, Jun; Yan, Ming; Xu, Jianming; Niu, Junqi; Liu, Jiajun; Watkins, Paul B.; Aithal, Guruprasad P.; Andrade, Raúl J.; et al. (Gastroenterology (New York, N.Y. 1943), 2019)
We performed a nationwide, retrospective study to determine the incidence and causes of drug-induced liver injury (DILI) in mainland China. We collected data on a total of 25,927 confirmed DILI cases, hospitalized from 2012 through 2014 at 308 medical centers in mainland China. We collected demographic, medical history, treatment, laboratory, disease severity, and mortality data from all patients. Investigators at each site were asked to complete causality assessments for each case whose diagnosis at discharge was DILI (n = 29,478) according to the Roussel Uclaf Causality Assessment Method. Most cases of DILI presented with hepatocellular injury (51.39%; 95% confidence interval [CI] 50.76–52.03), followed by mixed injury (28.30%; 95% CI 27.73–28.87) and cholestatic injury (20.31%; 95% CI 19.80–20.82). The leading single classes of implicated drugs were traditional Chinese medicines or herbal and dietary supplements (26.81%) and antituberculosis medications (21.99%). Chronic DILI occurred in 13.00% of the cases and, although 44.40% of the hepatocellular DILI cases fulfilled Hy’s Law criteria, only 280 cases (1.08%) progressed to hepatic failure, 2 cases underwent liver transplantation (0.01%), and 102 patients died (0.39%). Among deaths, DILI was judged to have a primary role in 72 (70.59%), a contributory role in 21 (20.59%), and no role in 9 (8.82%). Assuming the proportion of DILI in the entire hospitalized population of China was represented by that observed in the 66 centers where DILI capture was complete, we estimated the annual incidence in the general population to be 23.80 per 100,000 persons (95% CI 20.86–26.74). Only hospitalized patients were included in this analysis, so the true incidence is likely to be higher. In a retrospective study to determine the incidence and causes of DILI in mainland China, the annual incidence in the general population was estimated to be 23.80 per 100,000 persons; higher than that reported from Western countries. Traditional Chinese medicines, herbal and dietary supplements, and antituberculosis drugs were the leading causes of DILI in mainland China. [Display omitted]